Incidence of Hepatocellular Carcinoma in Patients With Chronic Hepatitis C Genotype III and Advanced Hepatic Fibrosis After Treatment With DAA - Waqar, Hamna; Babar, Fatima; Nawab, Sher; Chowdhry, Hira Amran; Irfan, Hamza; Fatima, Duaa (Biological and Clinical Sciences Research Journal, 2025)
Direct-acting antivirals with high efficacy and safety are effective in the treatment of cirrhotic and fibrosis patients with chronic hepatitis C patients. Objective: We conducted this study to assess the incidence of hepatocellular carcinoma in chronic hepatitis C patients genotype III with hepatic fibrosis or cirrhosis after the achievement of sustained viral response after treatment with direct-acting antivirals. Methods: A prospective study was conducted at the Department of Medicine, Arif Memorial Hospital, Lahore, from October 2023 to October 2024. A total of 500 CHC genotype III patients diagnosed with F3 and F4, who were undergoing treatment with direct-acting antivirals, were included in the study. Patients received a 3-month or 6-month course of DAA regimens. HCC was diagnosed by performing triphasic MSCT, and staging was done. Results: Out of 500 patients, 50 patients were diagnosed with HCC in the follow-up. HCC patients were predominantly elderly and male and had elevated AST, AFP, and bilirubin levels, as well as reduced platelet and albumin levels, compared to non-HCC patients. In cirrhotic patients, the HCC incidence per year was 2.920 per 100 people. Advanced age, male gender, increased AFP, and decreased albumin were among the predictors of HCC incidence in F4 patients. Conclusion: A reduced incidence of HCC was observed in patients with CHC fibrosis and cirrhosis who achieved SVR after treatment with DAAs.